1939
DOI: 10.1002/ange.19390524402
|View full text |Cite
|
Sign up to set email alerts
|

Synthesen in der Reihe der Steroide

Abstract: Is Steroide bezeichnet man eine Gruppe von Natur-A stoffen, die sich vom gleichen Ringgerlist Wie die Sterhe ahleiten, die also Derivate des hydrierten Cyclopentenophenanthrens (I) sind. Die Abkommlinge dieses einfachen Ringgertists haben in den letzten Jahren ein sehr allgemeines Interesse erlangt; nian darf wohl sagen, da5 die Vielseitigkeit der biologkhen Wirkung der Steroide einzig dastehend ist. In diese grofk Klasse von Naturstoffen gehoren die Sterine, die Gallensffuren, das antirachitische Vitamin, die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

1949
1949
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…EWG = electronwithdrawing group. [8][9][10][11][12][13] Our novel approach is based on the condensation of an aminocatalyst with an enal or 2,4-dienal to form either a dienamine or trienamine, respectively, which consist of a diene moiety attached to an activating and stereoinducing molecular handle. [20] A more recent development is the application of organocatalysis in targetoriented synthesis.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…EWG = electronwithdrawing group. [8][9][10][11][12][13] Our novel approach is based on the condensation of an aminocatalyst with an enal or 2,4-dienal to form either a dienamine or trienamine, respectively, which consist of a diene moiety attached to an activating and stereoinducing molecular handle. [20] A more recent development is the application of organocatalysis in targetoriented synthesis.…”
mentioning
confidence: 99%
“…[7] In the 1930s, Dane attempted this strategy, which was based on a cycloaddition between what became known as Danes diene and a dienophile. [8] Later Quinkert et al showed that the Diels-Alder reaction could be promoted by the application of a Lewis acid catalyst. [9] Recently, enantioselective versions of this approach, based on the activation of different dienophiles with chiral catalysts, have been reported (Scheme 1 a).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The diene 1 has been condensed with numerous other dienophiles [15][16][17][18][19][20][21][22][23][24][25]29], as has 16 [26][27][28]30]. A wide variety of dienes has been utilized, many of them by a Russian group associated with I. N. Nazarov.…”
mentioning
confidence: 99%